COMPUTATIONAL MODELS HYDROINJECTION INSTALLATION TUNNEL TYPE - Іванов, О. М.; Арендаренко, В. М. (Scientific Progress & Innovations, 2014)
The results of theoretical studies on the preparation of the computational model hydro spray tunnel designed for spraying high-pressure plants in the tunnel chamber. Studies were carried out using the theory of hydrodynamic and hydrostatic calculations for complex pipelines and multi-hydraulic systems. To achieve the objectives of the study were divided into components of hydraulic systems, each of which is a more simplified version of a complex pipeline. According to the results of computational studies were compiled analytical equations that determine the magnitude of hydraulic parameters at nodes and establish the relationship between the main components of the hydraulic system, and outlines the framework for the selection of a pressure pump for the amount of required pressure and flow.